Childhood exposure to domestic violence: can global estimates on the scale of exposure be obtained using existing measures? - Harris, Rebecca Jane; Channon, Andrew Amos; Morgan, Sara Afshar (Frontiers in Public Health, 2024)
Purpose Childhood exposure to domestic violence and abuse (DVA) can lead to major short- and long-term effects on the victim. Despite this, there is no accepted measure for children’s experiences, with most existing measures being validated only in high income countries and not in low- and middle- income countries. As a result, international statistics are not comparable. This paper seeks to critically appraise existing measures and discuss whether any are fit-for-purpose on a global scale. Method The COSMIN PROMs approach was followed to critically appraise and compare the appropriateness of measures. A comprehensive literature search was undertaken in seven journal databases for measures mentioned in formally peer-reviewed articles exploring childhood exposure to DVA. Results A literature search resulted in the identification of 10 measures and, following criteria to only keep original measures and remove modifications, four measures which have been validated cross-culturally are discussed in detail in line with the COSMIN PROMs criterion: The Child Exposure to Domestic Violence Scale, Children’s Perception of Interparental Conflict Scale, Juvenile Victimization Questionnaire and The Violence Exposure Scale for Children. Strengths and limitations of each are discussed, along with any validations undertaken not in the country of origin. Conclusion Despite childhood exposure to DVA being an urgent research priority worldwide, the current measures to explore the extent of the issue are not validated cross-culturally, leading to concerns about comparisons across different population groups. The development and implementation of interventions to reduce the levels and effects of exposure relies heavily on cross-cultural comparisons, which may indicate different strategies are needed in different contexts. The lack of these validated comparisons is constraining advances, and the paper advocates for further efforts to be made in this regard.